2007
DOI: 10.2320/matertrans.48.219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Shielding Gases and Power Waveforms on Penetration Characteristics and Porosity Formation in Laser Welding of Inconel 690 Alloy

Abstract: A high power Nd-YAG laser was used to perform bead-on-plate (BOP) welding on high viscosity Inconel 690 alloy plates of 3 mm in thickness with three different shielding gases (Ar, He, and N 2 ). Adopting a rectangular laser power waveform, four different peak-base power differentials (ÁP) were applied with a constant average power of 1.5 kW. A comprehensive investigation was performed into the influences of the shielding gas, the flow rate, and the value of ÁP on the characteristics of the resulting welds, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The samples welded under insufficient arc shielding gas had the greatest possibility for porosity 17 . In laser welding, transformation energy through keyhole mechanism was used, which resulted in maximum material melting.…”
Section: Macrostructures Of the Weldmentioning
confidence: 99%
“…The samples welded under insufficient arc shielding gas had the greatest possibility for porosity 17 . In laser welding, transformation energy through keyhole mechanism was used, which resulted in maximum material melting.…”
Section: Macrostructures Of the Weldmentioning
confidence: 99%
“…In contrast, it has been found that for lasers of shorter wavelengths such as YAG, fibre of disk laser (λ= 1.064 µm) the effect of shielding gas on process stability and weld geometry is minor and other parameters such as laser power density are dominant. For example, Kuo and Lin [11] reported that for a fixed set of welding parameters, similar penetration shapes and depths are obtained independently of the shielding gas employed. This is due to the fact that during Nd:YAG laser welding, laser energy absorption in the plume is very weak and therefore the plume volume has a lesser influence on the penetration depth.…”
Section: Introductionmentioning
confidence: 90%
“…One of his main conclusions is that Rayleigh absorption on nanoparticles is the dominant mechanism to consider in laser/vapour interaction. (Kuo and Lin, 2007) studied the influence of different shielding gas (argon, helium and nitrogen) during YAG pulsed laser welding of Inconel 690. They obtained similar weld beads dimensions and spatter generation whatever the protective gas and its flow rate but they reported that welding under helium generated a reduced vapour plume due to its higher thermal conductivity, and a faster expansion due to its lower density.…”
Section: Introductionmentioning
confidence: 99%